Predictors of beef calf temperament at weaning and its impact on temperament at breeding and reproductive performance. (19th January 2018) - Kasimanickam, VR; Abdel Aziz, RL; Williams, HM; Kasimanickam, RK
Contents: Two experiments were conducted to determine (i) factors influencing calf temperament at weaning, (ii) association between heifer–calf temperament at weaning and temperament at breeding and (iii) effect of heifer–calf temperament on pregnancy rate per artificial insemination (P/AI). In experiment 1, beef cows and their calves ( n = 285) from three farms were used. Sire docility estimated progeny difference (EPD) score, birth type (normal or assisted), calf gender, calf behaviour (during 1st 4 weeks) and calf health status (until weaning) were recorded. Cows and calves were assigned a temperament score (0—calm; 1—excitable), and all cows were given a body condition score (BCS, 1–9; 1—emaciated; 9—obese) at weaning. Calf's illness ( p < .05), low sire docility EPD score ( p < .05), altered gait ( p < .05), altered resting behaviour ( p < .01), reduced/no play behaviour ( p < .05) and cow excitable temperament ( p < .001) increased calf excitable temperament at weaning. In experiment 2, replacement heifer–calves ( n = 758) from 12 farms were assigned a temperament score at weaning and later at breeding. Blood from 40 calves at weaning and 31 heifers at initiation of synchronization (same animals) was collected by coccygeal venipuncture for determination of circulating cortisol and substance P concentrations. Heifers were assigned a BCS and reproductive tract score (RTS, 1–5; 1—immature, acyclic; 5—mature, cyclic), synchronized for fixed time AI, observed for oestrus and were artificially inseminated. Cortisol concentrations were increased in excitable heifer–calves compared to calm heifer–calves at weaning ( p < .05), and substance P was increased in excitable compared to calm females both at weaning and breeding ( p < .05). Low sire EPD docility score ( p < .01), heifer–calf excitable temperament at weaning increased excitable temperament at breeding ( p < .01). Controlling for BCS categories ( p < .01), oestrous expression ( p < .0001) and temperament at breeding by oestrous expression ( p < .05), the calf's excitable temperament at weaning ( p < .001) reduced P/AI (Calm, 62.7 (244/389) vs. Excitable, 53.4% (197/369); p < .01). In conclusion, selection of docile cows and sires with greater docility EPD score should be given consideration to reduce calf excitement. Temperament in beef female can be detected earlier in their life and could be used as a tool in the selection process and to improve their performances.